1968
DOI: 10.1126/science.162.3850.268
|View full text |Cite
|
Sign up to set email alerts
|

Lepidocrocite Iron Mineralization in Keratose Sponge Granules

Abstract: Reddish-brown granules embedded in the spongin fibers of some keratose sponges consist of very fine crystallites of poorly organized lepidocrocite, γ FeOOH. This is the first occurrence of crystalline iron mineralization in the phylum Porifera and the first indication of hard tissue formation among the Keratosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

1981
1981
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 4 publications
1
17
1
Order By: Relevance
“…33 The evidence of nanocrystalline iron mineralization among the Keratosa (horny sponges) was reported as well, thus proving the high affinity of the skeleton of sponges for iron compounds. 34 The spherical microparticles of lepidocrocite (g-FeO(OH)) were also reported previously: they were intimately attached to, and completely embedded into spongin bers, leaving little doubt as to their biological origin. 35 The reported results strongly suggested that the marine sponge skeleton is able to form direct bonds with other iron oxides such as hematite, and create novel hybrid materials.…”
Section: -5mentioning
confidence: 90%
“…33 The evidence of nanocrystalline iron mineralization among the Keratosa (horny sponges) was reported as well, thus proving the high affinity of the skeleton of sponges for iron compounds. 34 The spherical microparticles of lepidocrocite (g-FeO(OH)) were also reported previously: they were intimately attached to, and completely embedded into spongin bers, leaving little doubt as to their biological origin. 35 The reported results strongly suggested that the marine sponge skeleton is able to form direct bonds with other iron oxides such as hematite, and create novel hybrid materials.…”
Section: -5mentioning
confidence: 90%
“…In the genus Spongia the amount of iron is highly variable according to the habitat and to the age of the fibre. Several of the specimens analysed (sponges with low content of silica) showed this capacity of precipitating iron in the fibres of spongin; we have observed this in the horny sponge S28, Spongia agaricina, which exhibits a choanosome with a characteristic orange colour, and S30, Ircinia fasciculata, in which it was also observed previously the existence of lepidocrocite (Towe and Rützler, 1968). It is worth noting that, although both specimen accumulate Fe in large amounts, sponge S28 presents a rather low content of the other transition elements and the parallel trend (mentioned at the end of this section) observed among these elements is not observed in this specimen (see Figure 2).…”
Section: (2) Bromine (And Lead)mentioning
confidence: 54%
“…In the early 60s, ferritin’s respective cores were analyzed by X-ray diffraction (XRD) and electron diffraction (ED), revealing an amorphous and paracrystalline-to-crystalline mixture. Thus, it was named according to its similarity with its natural counterpart, ferrihydrite [21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…Ferritin cores of horse spleen analyzed by both HRTEM and ED displays a polyphasic structure [36,37]. Concerning the sponges, the only report on the presence of iron oxides particles (granules) was published by Towe et al in the late 60s and stated that an iron oxide polymorph, lepidocrocite (γ-FeOOH), was embedded in the spongin fibres of a keratose sponge (extracellularly) [21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation